Facts and Sensibilities: What Is a Psychoanalytic Innovation? - Govrin, Aner (Frontiers in Psychology, 2019)
Psychoanalytic innovation is easy to recognize but difficult to define. There is a dearth of literature exploring the nature of innovation in our field. My main thesis is that psychoanalytic innovation can be of two types. Psychoanalytic innovation of the first order is about new discoveries concerning facts related to the psyche, development, transference relations or psychopathology. It usually emerges as a development of insights from canonical psychoanalytic theory; offers an original explanation for a choice of empirical psychic phenomena hitherto unexamined; is perceived as creative and useful when it succeeds to reconceptualize the relations between the patient’s past, unconscious dynamics, and the transference relations; often resembles poetic expression and registers a truth we knew but did not yet put into words. When it is of the second order, psychoanalytic innovation challenges either methodological or philosophical assumptions held by psychoanalysis, without pretending to replace existing theories. It constitutes a “sensibility” that its adherents strive to incorporate into the existing corpus. I distinguish between two types of sensibilities: cultural -philosophical sensibility represented by the relational approach; and methodological sensibility represented by infant research, and neuropsychoanalysis. In the last part of the paper, I analyze psychoanalytic progress pointing to its merits and shortcomings.